ANALYZING CHALLENGES IN GRAMMATICAL KNOWLEDGE FOR EFL STUDENTS: Descriptive Quantitative Study - Nawira Nawira; Nunung Anugrawati; Muh. Arief Muhsin (Universitas Muhammadiyah Makassar, 2019)
This research aimed to find out what challenges were faced by EFL students at the English Department Muhammadiyah University of Makassar in their grammatical knowledge. This research used descriptive quantitative. The population of this research was the fourth semester of the English Department Muhammadiyah University of Makassar. The sample or the subject of this research was 50 students taken by accidental sampling technique. The researcher used the questionnaire as the instrument of this research. The result showed that challenges were mostly found by the students in developing their grammatical knowledge were: do not know how to organize the sentences to be a good paragraph, lack of self-confident, lack of vocabularies, lack of tenses and the biggest challenges were learning environment was too crowded, limited of time and lack of facilities.